QUIET REVOLUTION IN THE ORGANIZATION OF BRANCHES - A. Berkaeva (Вестник университета)
Economic and geopolitical crises have changed priorities in behavior of competitive firms and possession of a big share of today's market. It isn't the key to success in the future any more. Changes in external environment have demanded changes and in the internal environment of the organizations and branches directed to disclosure of their intellectual capital and realization of key competences and management of knowledge.